Malaysian Democratic Dilemmas in the Era of Najib Razak - Radzuwan Syed Sopi, Saiyid; Fauzi Abdul Hamid, Ahmad (International Journal of Psychosocial Rehabilitation, 2020)
The objective of this research is to see how Prime Minister Najib Razak has manipulated the concept of democracy in fulfilling his needs to remain in power. The focus of this study is to find out why Najib is willing to exploit state institutions such as the bureaucracy, police departments, and anti-corruption agency, and cooperate with cabinet members to ensure that he perpetually clings to power. In principle, most third-world elites are quite happy to dismantle existing institutions (parliament, elections) in the interests of continued rule. Besides that, those who are already in power often view institutions more as obstacles and less as facilitators of effective rule. This research finds those who support and protect Najib realize that some actions of their boss are illegal, but they pretend to support him in order to fulfill their selfish desires. A leader will preserve his power when most of his supporters have become blinded by the trappings of power. They know Najib’s faults but still support him. Whatever wrongs Najib has done, they still support him.